Research on swimming force model of athletes based on Bernoulli's law - Wang, Q.; Yang, Y.; Meng, X.; Sun, X.; Qi, J. (Journal of Frontiers in Art Research, 2021)
There are many kinds of postures in swimming, but different postures have a significant effect on the speed at which swimmers move forward. This paper takes the swimming environment as the ideal state, without considering the change of the swimmer's leg strength during the swimming process and the influence of other forces not considered in addition to this article, we can accurately solve the best posture when swimming, so that the swimmer swims as fast as possible. Firstly, by combining Bernoulli's law and fluid continuity theorists, this paper establishes the lift model. Then, we solve the relationship between the angle of the athlete's body axis and horizontal surface and the swimming speed change. Finally, the optimal swing amplitude of the athlete's body axis and horizontal surface is derived, which helps the coaches improve the athlete's swimming posture.